2022
DOI: 10.1186/s12885-022-09325-6
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial chemoembolization combined with camrelizumab for recurrent hepatocellular carcinoma

Abstract: Purpose To evaluate the efficacy and safety of transarterial chemoembolization (TACE) combined with camrelizumab (hereafter, TACE-camrelizumab) in the treatment of patients with recurrent hepatocellular carcinoma (R-HCC) after curative resection. Patients and methods R-HCC patients who underwent TACE plus camrelizumab or TACE-alone from January 2016 to August 2021 were retrospectively evaluated. Patients were assessed for tumor response, progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 36 publications
0
25
1
Order By: Relevance
“…Previous studies have proved that TACE combined with carrelizumab has certain clinical efficacy in the treatment of advanced HCC. 20 , 21 In this study, the median TTP and OS of the whole cohort were 7.3 months and 14.3 months, respectively, which was better than previous studies using TACE or camrelizumab alone. 22–24…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Previous studies have proved that TACE combined with carrelizumab has certain clinical efficacy in the treatment of advanced HCC. 20 , 21 In this study, the median TTP and OS of the whole cohort were 7.3 months and 14.3 months, respectively, which was better than previous studies using TACE or camrelizumab alone. 22–24…”
Section: Discussioncontrasting
confidence: 50%
“…Previous studies have proved that TACE combined with carrelizumab has certain clinical efficacy in the treatment of advanced HCC. 20,21 In this study, the median TTP and OS of the whole cohort were 7.3 months and 14.3 months, respectively, which was better than previous studies using TACE or camrelizumab alone. [22][23][24] Subgroup analysis showed that for HCC patients with hypervascularity and RCCEP response, the median TTP and OS were 10.6 months and 19.3 months, respectively, which was superior to other groups of patients in the cohort study.…”
Section: Discussionmentioning
confidence: 48%
“…The combination of ICIs and targeted drugs has significantly improved the clinical outcomes of HCC patients [ 29 31 ]. In the same direction, the combination of TACE plus camrelizumab increased the PFS of advanced HCC patients to 9 months [ 5 ]. Nevertheless, predicting the efficacy of HCC patients receiving ICIs remains a clinical challenge with a definite positive outcome in the quality of patient care.…”
Section: Discussionmentioning
confidence: 99%
“…guidelines as the first-line treatment for advanced HCC, which could extend OS to 19.2 months [3,4]. Yusheng et al reported that the median progression-free survival (mPFS) of advanced HCC patients receiving transarterial chemoembolization (TACE) plus camrelizumab was 9 months [5]. In addition, in a randomized controlled study of operable HCC, patients who received adjuvant TACE had a higher threeyear OS rate compared to patients who underwent surgery alone (85.2% vs. 77.4%; p = 0.04) [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation